ONLINE CONSUMER REVIEW PADA CLUSTER GENERASI MILENIAL - NAENSHI NURLIANA SARI; COK GEDE PUTRA YUDISTIRA; I WAYAN EDI ARSAWAN; KASIANI KASIANI (Universitas Mahasaraswati K. Mataram, 2022)
This study purposed to identify the factors of online consumer reviews that effecting hotel booking intention of Millennials in Badung city. This research uses a quantitative approach. The sampling technique used was the Non-Probability Sampling method, namely purposive sampling with a total number of respondents are 385 respondents of Millennials in Badung city. The data analysis technique of this research was multiple linear regression analysis which was processed using the SPSS 21 program. The result showed a significantly positive relationship between the usefulness of online reviews, timelines of online reviews, and comprehensiveness of online reviews on respondents' hotel booking intentions. A positive but not significant relationship between the positive valence of online reviews on respondent's hotel booking intentions. While the impacts of the volume of online reviews and negative valence of online reviews upon hotel booking intentions were negative and not statistically significant